An acetyl fentanyl death in Western Australia - Moss, D.; Brown, David; Douglas, B. (Taylor & Francis Ltd., 2019)
Post-mortem case details, including toxicology, of deaths involving novel psychoactive substances (NPS) are limited due to the relatively recent emergence of NPS as a global problem. Acetyl fentanyl, an illicit fentanyl analogue, is no exception, with its prevalence being documented since 2013. This case report seeks to provide pathology and toxicology findings of a sudden death attributed to acetyl fentanyl use. Following injection of acetyl fentanyl, a 24-year old male died suddenly. The autopsy indicated pulmonary oedema and congestion, and early aspiration pneumonia as the only notable findings. Preliminary toxicology testing was inconclusive until drug paraphernalia found at the scene of death was shown to contain acetyl fentanyl. Subsequent toxicological analysis of the post-mortem samples revealed an acetyl fentanyl blood concentration of approximately 400 µg/L and a liver concentration of approximately 3000 µg/kg.